Predictive Factors of Essential Satisfaction in Pedagogy Students of the Universidad Surcolombiana - Casadiego Cabrales, Alix María (2018)
Asking oneself about the satisfaction of life within a faculty of education brings us closer to the expectations of the future trainers of society. From this perspective, the objective of this study is to analyze which factors predict life satisfaction of students at Surcolombiana University and compare them to other constructs based on the sex variable. An analytical and transversal study was carried out with 408 participants. Data were collected through the Adolescent Life Satisfaction Scale (ESVA), Spanish version of the Trait Meta-Mood Scale (TMMS-24), Assertive Interpersonal Scheme Questionnaire (AISQ) and the Self-concept (Form AF- 5). Results showed that life satisfaction was predicted by the family dimension of AF-5 (self-concept) (β = .274 [.210 - .324]; p < .001) and the dimension of emotional repair of TMMS-24 (emotional intelligence) (β = .201 [.144 - .231], p < .001). There are no significant differences depending on the sex variable. Results are discussed in relation to the existing literature.